Platyonitis oberthueri Janssens, 1942 and Epionitis tarsatus Balthasar, 1942 (Coleoptera: Scarabaeidae: Scarabaeinae: Onitini) — synonymy confirmed - Bezděk, Aleš; Sládeček, František X. J. (Zootaxa, 2012)
The genus Epionitis Balthasar, 1942 and species Epionitis tarsatus Balthasar, 1942, were described from a single female from “Ost-Afrika, Ussambara” [= NE Tanzania] (Balthasar 1942). Earlier the same year, Janssens (1942) established the new genus Platyonitis for P. oberthueri Janssens, 1942 based on two specimens (holotype male and paratype female) from “Manica” [= Manica, Mozambique]. Krikken (1974) synonymized both these names based on study of Janssens’s types and Balthasar’s description. However, he was not able to study the holotype of E. tarsatus, so he could not fully confirm the synonymy of both type species. Krikken (1974) stated on p. 202: “Several descriptive details of E. tarsatus, based on a single female, are strongly indicative of a synonymy, but since no information on the characteristic shape of the middle femora is given by Balthasar, I prefer to postpone my final decision on the matter”.